Sonochemical synthesis of graphene oxide sheets supported Cu2S nanodots for high sensitive electrochemical determination of caffeic acid in red wine and soft drinks. (1st February 2019) - Chen, Tse-Wei; Rajaji, Umamaheswari; Chen, Shen-Ming; Govindasamy, Mani; Paul Selvin, S. Steplin; Manavalan, Shaktivel; Arumugam, Rameshkumar
Abstract: A nanocatalyst based on copper sulfide nanodots grown on graphene oxide sheets nanocompsite (Cu2 S NDs@GOS NC) was synthesized by a simple sonochemical techniques and applied in electrocatalytic sensing of caffeic acid (CA). The structural and elemental aspects of Cu2 S NDs@GOS NC were analyzed by XRD, XPS, FE-SEM, TEM, and EDX. The interfacial electron transfer property of the composite was probed by EIS. The nanocompsite modified SPCE showed excellent electrocatalytic ability towards redox reaction of CA. Under optimized conditions, Cu2 S NDs@GOS NC modified electrode delivered rapid and sensitive amperometric responses towards CA. The linear range was 0.055–2455 μM. Interestingly, the modified electrode able to detect nanomolar concentration of CA and the detection limit is 0.22 nM, which surpassed the detection limits of many existing methods. The Cu2 S NDs@GOS NC/SPCE is able to quantify the amount of CA present in carbonated soft drinks and red wine without sample pretreatments. Highlights: Sonochemical synthesis of graphene oxide supported copper sulfide nanodots (Cu2 S NDs@GOS nanocomposite). Characterisation by XRD, XPS, FE-SEM, HR-TEM, EDX, mapping methods and EIS. Electrocatalytic behavior of Cu2 S NDs@GOS towards caffeic acid. Selectivity, repeatability, reproducibility, stability. Practicality in soft drinks and fruit juice samples, applicable in food additive analysis.